Rare Case Giant Cystic Mediastinal Tumor (Mature Teratoma) in 57 years old Woman - Akbar, Jimmy Akbar; Parsama, Ngakan Putu Putra; Erawati, Dini Rachma; Wardhana, Koernia Kusuma; Yudhanto, Hendi Setyo (Universitaas Brawijaya, 2020)
Background : Incidence of mediastinal teratoma 8,5 - 13,6% of all patients in mediastinal tumor. Teratomas are most common in young adults. Mediastinal teratoma is rarely present clinical manifestation. The clinical manifestation present along with increasing size of mass and also reported with chest pain, back pain, shortness of breath and febrile caused by chronic pneumonia. Rupture of a mediastinal teratoma can cause pleural effusion, empyema and cardiac tamponade. CT is first modality of choice for tumour diagnosis. Mature teratoma is a type of benign tumor, most patients will recovery after complete resection.Case Report : We report one case at Dr. Saiful Anwar hospital, an elderly woman, 57 years old with mediastinal teratoma, whose formerly differential diagnosed with empyema. On the diagnostic test found no evidence of empyema but leads to loculated cloudy pleural effusion. Physical and supporting examination showed anterior mediastinal tumors. Based on the CT-Scan and thorax sonography concluded that is a cystic mass on anterior right hemithorax dextra. The patient performed thoracotomy and eksploration with the final diagnosis of giant cystic mediastinum tumour, with the histopathology is mature teratoma. Conclusion: In this patient, the diagnosis of mediastinal cystic mature teratoma with loculated pleural effusion proven through a multidisciplinary approach covering the pulmonology, thoracic and cardiovascular surgery, radiology and histopathology. Key words : Mediastinal tumour, Mature teratoma